Reversal reaction with nodules clinical manifestations that initially diagnosed as erythema nodosum leprosum in borderline lepromatous leprosy - Tsaqilah, Laila; Achdiat, Pati Aji; Gunawan, Hendra (UI Scholars Hub, 2020)
Background: The reversal leprosy reaction generally manifest as larger, swollen, red and shiny the pre-existing skin lesions which are accompanied with pain. This reaction can be manifest as infiltration and nodules which resembles the features of erythema nodosum leprosum (ENL) leprosy reaction. Case Illustration: We present a case of 26-year-old woman with erythematous nodules on almost all the body since two weeks ago. She had pre-existing erythema plaque on the right elbow became more erythematous and arouse with partially felt pain, fever, and malaise. Nodule lesions in BL leprosy with reaction need to be distinguished between ENL and reversal reaction because they may affect therapy and prognosis. Discussion: The patient was diagnosed as BL leprosy with ENL reaction erythematous nodules on the face, both upper and lower arms, upper and lower limbs, knees, that partially felt pain, but after more careful history and histopathologic examination of the lesions, the nodules didn’t match to the histopathologic features of ENL reaction. Correlation between the clinical and histopathological findings in the form of acid fast bacilli (AFB) and granulomatous inflammation grenz zone with epithelioid cells and lymphocyte cells infiltrations in the dermis established the diagnosis of BL leprosy with reversal reaction. Conclusion: Erythema nodule lesions in leprosy can be an ENL or reversal reaction or a leprosy lesion in type BL leprosy. Reversal reaction should always be considered when diagnosing a skin-colored nodule in leprosy. Appropriate clinical and histopathological findings of the skin-colored nodules are needed to establish the definite diagnosis of reversal reaction.